Mut'ah Marriage Law in Perspective of Sayyid Husain Al-Thaba’thabaí and Their Relevance with Family Law in Indonesia - Qohar, Abd; Zaki, Muhammad; Faizal, Liky; Rofi'i, Hilmi Yusron (Institut Agama Islam Negeri Curup, 2022)
This study aims to examine Al-Thaba’thabaí 's thoughts on Mut'ah marriage and its relevance to family law in Indonesia. This research is a type of library research by descriptive-analytical approach. The primary data in this study are the Qur'an, Hadith, books by Al-Thaba’thabaí, the 1945 Constitution, Law Number 1 of 1974 concerning National Marriage Law, PP. Number 9 of 1975 as the implementing regulation of Law no. 1974, and INPRES No.1/1991 on the Compilation of Islamic Law (KHI). This study uses deductive thinking techniques and the data analysis uses maqashid sharia theory. The results show that Al-Thaba’thabaí 's thoughts on the permissibility of Mut'ah Marriages are not relevant to the purpose of marriage and the purpose of making legislation. As the purpose of making the law is the value of justice, usefulness, and legal certainty, besides the law is also made to create benefit in society. Al-Thaba’thabaí’s thought regarding Mut'ah Marriage must be rejected because it violates the values of the legal objectives, namely justice, benefit, and legal certainty, and also harms the values of benefit. To provide firmness to prohibit the practice of mut'ah marriage in Indonesia, it is necessary to amend Article 2 of Law Number 1 of 1974 concerning Marriage to